2020
DOI: 10.3748/wjg.v26.i35.5343
|View full text |Cite
|
Sign up to set email alerts
|

Updated bone mineral density status in Saudi patients with inflammatory bowel disease

Abstract: BACKGROUND Little is known about inflammatory bowel disease (IBD) burden and its impact on bone mineral density (BMD) among adult patients in Saudi Arabia. To the best of our knowledge, our study is the only study to give an update about this health problem in adult Saudi patients with IBD. IBD is a great risk factor for reduced BMD due to its associated chronic inflammation, malabsorption, weight loss and medication side effects. Consequently, screening for reduced BMD among patients with IBD is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Interestingly, according to the research conducted among Saudi patients, individuals with CD presented reduced BMD more frequently than UC patients. Osteoporosis, in turn, affected 37% and 25% of CD and UC patients, respectively, in comparison to osteopenia which was diagnosed in 19% and 7% of CD and UC patients, respectively [12]. Our study demonstrated significant differences in BMD, the T-score and Z-score of the femoral neck and lumbar spine (L1-L4) between patients suffering from CD, UC and the healthy subjects.…”
Section: Discussionmentioning
confidence: 57%
“…Interestingly, according to the research conducted among Saudi patients, individuals with CD presented reduced BMD more frequently than UC patients. Osteoporosis, in turn, affected 37% and 25% of CD and UC patients, respectively, in comparison to osteopenia which was diagnosed in 19% and 7% of CD and UC patients, respectively [12]. Our study demonstrated significant differences in BMD, the T-score and Z-score of the femoral neck and lumbar spine (L1-L4) between patients suffering from CD, UC and the healthy subjects.…”
Section: Discussionmentioning
confidence: 57%
“…Bone mass loss is a frequent complication in patients with UC[ 22 - 24 ] and with a higher prevalence when compared to that in healthy controls[ 25 ]. Greater bone fragility increases the risk of fractures, and consequently morbidity and reduced quality of life for patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Gulyás et al [ 8 ] TNF-α inhibition slowed down generalized bone loss in rheumatoid arthritis and ankylosing spondylitis. Effect of anti TNF therapy on bone metabolism was not confirmed by Ewid et al [ 1 ] hence, the effect is questionable in IBD.…”
Section: To the Editormentioning
confidence: 93%
“…We read with a great interest the study by Ewid et al [ 1 ], that evaluated the connection between inflammatory bowel disease (IBD) and bone mineral density (BMD) in a sample of adult Saudi patients with IBD from a single center.…”
Section: To the Editormentioning
confidence: 99%